Etanercept (Enbrel®) alternative storage at ambient temperature - Shannon E; Daffy J; Jones H; Paulson A; Vicik SM (Dove Medical Press, 2017)
Edel Shannon,1 Joanne Daffy,2 Heather Jones,3 Andrea Paulson,4 Steven M Vicik5 1Global Chemistry, Manufacturing, and Controls Regulatory, 2Contract Operations Quality Assurance, Pfizer Ireland Pharmaceuticals, Clondalkin, Dublin, Ireland; 3Medical Affairs, Pfizer, Collegeville, PA, USA; 4Pharmaceutical Research and Development, 5Global Supply Product Portfolio Management, Pfizer Biotech, Andover, MA, USA Background: Biologic disease-modifying antirheumatic drugs, including tumor necrosis factor inhibitors such as etanercept (Enbrel®), have improved outcomes for patients with rheumatic and other inflammatory diseases, with sustained remission being the optimal goal for patients with rheumatoid arthritis. Flexible and convenient treatment options, compatible with modern lifestyle, are important in helping patients maintain treatment and manage their disease. Etanercept drug product (DP) is available in lyophilized powder (Lyo) for solution injection, prefilled syringe, and prefilled pen presentations and is typically stored under refrigerated conditions. We aimed to generate a comprehensive analytical data package from stability testing of key quality attributes, consistent with regulatory requirements, to determine whether the product profile of etanercept is maintained at ambient temperature. Methods: Test methods assessing key attributes of purity, quality, potency, and safety were performed over time, following storage of etanercept DP presentations under a range of conditions. Results: Results and statistical analysis from stability testing (based on size exclusion high-performance liquid chromatography, hydrophobic interaction chromatography, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis Coomassie) across all etanercept presentations (10 and 25 mg/vial Lyo DP; 25 and 50 mg prefilled syringe DP; 50 mg prefilled pen DP) showed key stability-indicating parameters were within acceptable limits through the alternative storage condition of 25°C±2°C for 1 month. Conclusion: Stability testing performed in line with regulatory requirements supports a single period of storage for etanercept DP at an alternative storage condition of 25°C±2°C for up to 1 month within the approved expiry of the product. This alternative storage condition represents further innovation in the etanercept product lifecycle, providing greater flexibility and enhanced overall convenience for patients. Keywords: etanercept, ambient, storage, temperature, stability